(3HOGjI GdShd ajeG SfM ef JaVjd GdQShds - (3YR GdOjf YHO GdYRjR Hf YHO GdSdGe Hf CHh GdbGSe Hf GdMSf GdSdej GdOeTbj, GdYR Hf YHO GdSdGe,J (B660 (3g` s
(3ChdgG (B:s
(3bGd Gddg JYGdi dfHjfG UdhGJ Gddg hSdGeg Ydjg (B: (3hCfRd Ydjc GdcJGH hGdMceI s
(3BNQgG (B:s
(3hfMf fSCd Gddg Hefg hcQeg Cf jhabfG dGJHGY QShdg ai SfJg hWQjbJg hLejY CMhGdg s
(3Vef eLehY , JQJjHgG (B: (3ef U (B174 - (3U(B179s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B21s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B430 ; (3HQhcdeGf edMb (B- (3GdLRA (B1 - (3U (B767 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B41 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs